Análise da influência do monitoramento OTDR em WDM-PON: um estudo baseado em simulação - COSTA, Ulisses Weyl da Cunha (Universidade Federal do Pará, 2014)
Passive Optical Networks are increasingly diffused as a broadband access technology. Due to their importance, such networks demands continue supervision scheme. Different techniques could be employed for Optical Network Supervision, among them those using reflectometry have highlighted, because it offer low cost when compared with other monitoring methods and do not require intervention in the user’s home. On the other hand, when doing monitoring, it is expected that this action does not influence the information signal transmitted to the subscriber. In this context, this work aims to quantify, through simulations, how the technique of time domain optical reflectometry interferes on the transmission of a WDM-PON network.